A Social and Spatial Analysis of Madison's Bicycling Community - Brubaker, Martin; Wright, Kirby; O'Halloran, Brenna; Wilson, Alissa (My University, 2016)
For many cities across the United States biking is not just a leisurely activity; it is a means of transportation, exercise, and an important staple that helps form a sense of identity and community. This study looks at Madison, Wisconsin’s bicycle community and examines how infrastructure influences the overall bikeabilty and social structure of the city. While infrastructure is an important underlying factor in determining the safety and effectiveness of a city, this study also analyzes how infrastructure can impact gender divides, racial composition, and safety concerns. All of these factors play into the accessibility and management of a bicycle community. Our research consisted of survey data from cyclists at the Wisconsin Bike Federation and cyclists on and off campus, as well as interviews with two UW students and Dave Cieslewicz, executive director at the Wisconsin Bike Federation and former Mayor of Madison. By examining survey and interview data, graphs based on demographics and networking were created, confirming that Madison, Wisconsin has great rating as a bike-friendly community and is considered one of the better cities for biking in the United States. In particular, our engineering of streets and bike paths/routes helps push Madison, Wisconsin ahead of the curve.
Includes tables, figures, appendices, bibliography
Keywords: Transportation; Community; Bicycling; Spatial analysis; Wisconsin; Madison